2005
DOI: 10.1097/01.brs.0000155419.24198.35
|View full text |Cite
|
Sign up to set email alerts
|

Interbody Device Shape and Size Are Important to Strengthen the Vertebra–Implant Interface

Abstract: The cloverleaf-shaped indentor displayed an improved strength and stiffness profile when compared to oval or kidney-shaped indentors of similar surface areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 17 publications
6
70
0
Order By: Relevance
“…The average failure loads of 2017 N and 2207 N for PMMA and PEEK cages in this study ( Table 2) were comparable to the values reported in previous literature, 5,[8][9][10] however, there are considerable differences in the failure loads obtained by different embedding methods of the specimens. The average segmental stiffness of 557 N/mm of group of PEEK spacers and the higher stiffness of 1373 N/mm in group of novel PMMA cement spacers compared well with the values reported in.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The average failure loads of 2017 N and 2207 N for PMMA and PEEK cages in this study ( Table 2) were comparable to the values reported in previous literature, 5,[8][9][10] however, there are considerable differences in the failure loads obtained by different embedding methods of the specimens. The average segmental stiffness of 557 N/mm of group of PEEK spacers and the higher stiffness of 1373 N/mm in group of novel PMMA cement spacers compared well with the values reported in.…”
Section: Discussionsupporting
confidence: 79%
“…The average segmental stiffness of 557 N/mm of group of PEEK spacers and the higher stiffness of 1373 N/mm in group of novel PMMA cement spacers compared well with the values reported in. 5,8,10 The average failure displacements of 5,56 mm of PEEK group and 2.80 mm of PMMA group are in the ranges reported in. 1,10 Surprisingly, the load bearing capacity of segments is inversely proportional with the bone quality of vertebrae in the case of PMMA cages, mainly centrally, while the load bearing of PEEK spacers is strongly related to the bone quality, mainly subcortically ( Figure 3 and Table 3).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…in osteoporosis, application of the standard fixation approaches using interbody implants can be inadequate due to the reduced bone quality and the degeneration of the vertebral endplates and may lead to damage of the bone tissue at the interface via excessive subsidence of the spacer, yielding to further complications, pain, instability and potentially to the collapse of the motion segment. [1][2][3][4] A novel method aims at circumventing the drawbacks of the conventional techniques by using cement spacers. In the frame of this approach bone cement is injected into the gap of the removed parts of the degenerated intervertebral disc and the remaining space is filled with graft material to foster fusion of the adjacent vertebrae.…”
Section: Introductionmentioning
confidence: 99%